Illustrative Book Design to Introduce the Indonesian Sign Language System as an Inclusive Educational Material - Kurniawan, Muchlis Sopian; Kharishma, Vidya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
Education is the right of every human being, including children with special needs, such as deaf or hard-of-hearing children. Inclusive schools are educational institutions where children with special needs can learn alongside normal children. The Indonesia Natural School (INS) is one of the formal educational institutions in Depok City. It is an inclusive school where deaf children are also students. According to INS, it is common for deaf students to experience communication difficulties, which impedes interaction in the school environment. Difficulties are not only experienced by deaf students but also by normal students who have obstacles when they want to interact with deaf children. The objective of this research is to create educational material that introduces INS students to the Indonesian Sign Language System (SIBI). The media chosen for this study is the SIBI System illustration book, which describes various SIBI signs. The research method chosen is descriptive qualitative. The process of collecting data includes interviews, observations, and document reviews. After analyzing the data collected, it will be used as a reference to design an illustrated book about SIBI. The results of this research are illustrated books that will be used as literacy media as a reference for INS students to learn SIBI. Students can find them in school facilities like classrooms and libraries. It is hoped that through this research, normal students at INS schools will have access to media that makes it easier for them to understand and practice communicating with deaf children. The results of this study are expected to be accessible to students and teachers at INS and measured for their success in enhancing understanding and communication between normal students and students with hearing impairments.